Hungarian Monitoring, 2 July 1988 . [Magyar rádiófigyelő], 1988. július 2 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Summary of and international reactions to Moscow Party conference Domestic Affairs: - Károly Grósz's forthcoming trip to Romania - Hungarian-Soviet economic cooperation - Károly Grósz receives departing commander of Soviet troops stationed in Hungary - Monday's demonstration outside Romanian embassy - Interview with Imre Pozsgay - Circumstances surrounding Csaba Kesjár's death - Albert Szentgyörgyi conference in New York Economy: - Rezső Nyers makes statement on significance of private sector Külpolitika - A moszkvai pártértekezlet összefoglalója és nemzetközi visszhangja Belpolitika: - Grósz Károly esedékes romániai útja - Magyar-szovjet gazdasági együttműködés - Grósz Károly fogadta a Magyarországon állomásozó szovjet csapatok távozó parancsnokát - A román nagykövetség előtti hétfői tüntetés - Pozsgay interjú - Kesjár Csaba halálának körülményei - Szentgyörgyi Albert szimpózium New Yorkban Gazdaság: - Nyers Rezső a magánszektor jelentőségéről nyilatkozik